Transaction strategy of virtual power plants and multi-energy systems with multi-agent Stackelberg game based on integrated energy-carbon pricing - Yan, Yanyu; Xie, Shiwei; Tang, Jianlin; Qian, Bin; Lin, Xiaoming; Zhang, Fan (Frontiers in Energy Research, 2024)
A virtual power plant (VPP) has the ability to aggregate numerous decentralized distributed energy resources using advanced control technology, offering a promising approach for low-carbon development. In order to enhance the VPP’s contribution to reducing carbon emissions, a bi-level framework is proposed that incorporates an integrated energy-carbon price response mechanism. This model allows VPPs to participate in a multi-energy system through a multi-agent Stackelberg game framework. Initially, a transaction model is established where the power distribution system operator and the gas distribution system operator act as leaders, while the virtual power plant operator acts as a follower in the multi-energy system. Subsequently, an integrated energy-carbon pricing method, rooted in carbon emission flow theory, is introduced to encourage VPPs to proactively adjust their energy-use and trading strategies within multi-energy systems, thereby promoting multi-principal interactive trading. To achieve a distributed solution among multiple entities while maintaining the privacy of each entity’s information, the adaptive step-size alternating direction multiplier method is employed. The feasibility and effectiveness of the proposed model and method are then demonstrated through case studies.